STUDI FENOMENOLOGIS LIVE IN DESA WISATA (STUDI KASUS MAHASISWA BSI YOGYAKARTA) - Ani Wijayanti (Universitas Bina Sarana Informatika, 2014)
Live experience at tourism village give a major influence on the formation of the tourists image. The image formed, greatly influence the decision-making process to make repeat bussiness or not at all. This study used a qualitative research design with a phenomenological study approach, by outlining or exploit live experience in the tourists through three stages, namely intuiting, analyzing and describing. The population were all live in participants in the tourism village in Brayut, on December 4 s / d January 5, 2014, which is totaled 150 participants, Yogyakarta BSI students who are following the live activities in the tourism Brayut village. Samples were obtained six criteria of participants, and the results of research, there are several indicators of dissatisfaction, namely the lack of a safety guarantee for the participants, the event is less attractive packaging, lack of good coordination of the committee, as well as the lack of infrastructure, covering the less knowledgeable, equipment not supplicants for all participants, homestay locations away from the center of the show. In this case the manager of Brayut village tourism have an important homework, to look at the dissatisfaction indicators which is founded by researcher in the field. The stakeholder must evaluate the village tourism and decide the next strategic steps to improve the services quality for the visitors, which is influence the behavior of subsequent travelers, as revealed by Schiffman and Kanuk (2007), customer behavior is a process through which a person in finding, purchasing, using, evaluating and acting after using the product, service or idea which is expected to meet the needs.